The new kid on the block : poems - Prelutsky, Jack.; Stevenson, James, 1929-2017 (New York : Scholastic, 1984)
Humorous poems about such strange creatures and people as Baloney Belly Billy and the Gloopy Gloopers.
Includes index.
Keywords: Children's poetry, American; American poetry; Humorous poetry